The Responsibility of Mudharib toward the Customer Fund of Shahibul Maal in a Financing Agreement - Agung Prabowo, Bagya; ., Nurjihad; Fairuzzaman, Fahmi (KnE Social Sciences, 2023)
The Association of State-Owned Banks (Himbara) has taken over the ownership of three Islamic banks, Bank Rakyat Indonesia Syariah, Bank Syariah Mandiri, and Bank Negara Indonesia. As a result of this, the government expects Islamic finance to be more competitive in the digital age. To comply with the legislation, deposits made by customers who deposit money also go to the combined bank. According to the explanation of Article 28 of Law No. 10 of 1998 on Banking, the responsibility of the bank for customer funds in connection with a merger of banks is typically regulated. The merger carried out by the bank must not impair the interests of the customer. However, neither the Banking Law nor other pertinent laws and regulations provide additional guidance on the types of legal remedies that consumers negatively affected by this merger could use. This study aimed to ascertain the obligation of the Mudharib under the Mudharabah financing arrangement to Shahibul Maal funds following the merger into an Indonesian Sharia Commercial Bank. The results showed that the mudharib must continue the mudharabah financing agreement and continue to offer profit sharing in accordance with the terms of the shahibul maal funds in the mudharabah financing agreement following the merger into Bank Syariah Indonesia. Keywords: Merger, Mudharabah, Legal Protection